The Influence of Democratic Leadership and Organizational Climate on The Performance of Teachers - Siti Umaimah; Musfiqon Musfiqon; Benny prasetiya (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The purpose of this study is to determine the influence of democratic leadership and organizational climate on teacher performance. This research used survey methods, while the research hypothesis testing utilized multiple regression tests. The research samples were 67 teachers in Aisyiyah Bustanul Atfal Kindergarten in Probolinggo. The results of this study indicates that there is a significant influence between democratic leadership and organizational climate on teacher performance. The coefficient of determination shows that 20.5% of teacher performance is determined by democratic leadership and organizational climate